(untitled) (Research, Society and Development, 2020)
Suicide is configured as a serious public health problem that affects different parentage, social classe and age range. In the last decades, it has been observed an increasement in this phenomenon among the young population, currently representing the largest group of risk. Due to the recognition of adolescence as a period of several changes, which can generate periods marked by conflicting feelings and the identification of the school environment as a potential for reaching these young people. This study purpose is to identify suicide prevention strategies for adolescents in school environments. It used as methodology, the integrative literature review, with research in the Medline database, between the period of 2009 to 2019, with the combination of the following descriptors: adolescence, prevention, school, suicide.It was identified 19 articles that described 14 prevention strategies. Within the analyzed interventions, there is the importance of training employees at school to identify risk and intervention (gatekeeper training) and screening students to detect the risk. The literature review carried out made it possible to identify two levels of suicide prevention (universal and indicated), as wel as three most common types of strategies used (screening, gatekeeper training and psychoedication). It was concluded that the strategies can contribute to the increase of knowledge about suicide and mental health among adolescents and school employees and the identification and reduction of risk behavior among students.